The history of South American octodontoid rodents and its contribution to evolutionary generalisations - Verzi, Diego Héctor (2015)
Fil: Verzi, Diego Héctor. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Vertebrados; Argentina